The Adaptive Monte Carlo Toolbox for Phase Space Integration and Generation (Communications in Computational Physics, 2019)
An implementation of the Monte Carlo (MC) phase space generators coupled with adaptive MC integration/simulation program FOAM is presented. The firstprogram is a modification of the classic phase space generator GENBOD interfacedwith the adaptive sampling integrator/generator FOAM. On top of this tool the algorithm suitable for generation of the phase space for an reaction with two leadingparticles is presented (double-peripheral process with central production of particles).At the same time, it serves as an instructive example of construction of a self-adaptivephase space generator/integrator with a modular structure for specialized particlephysics calculations.